Immuno-Isolating Dual Poly(ethylene glycol) Capsule Prevents Cancer Cells from Spreading Following Mouse Ovarian Tissue Auto-Transplantation. Issue 1 (2019) - Day, James R.; David, Anu; Long, Catherine; Bushnell, Grace G.; Woodruff, Teresa K.
No abstract available